(untitled) (Eurasian Medical Research Periodical, 2026)
Severe acute pancreatitis (SAP) carries a mortality of up to 40% and its clinical trajectory is only partially explained by conventional scoring systems. Genetic variation in pathways governing vascular response, tissue remodelling, oxidative stress, protease inhibition and drug metabolism may determine individual susceptibility to pancreatic necrosis. The present study aimed to quantify the prognostic contribution of five candidate single-nucleotide polymorphisms (SNPs) - VEGFA G634C (rs2010963), MMP9 Gln279Arg (rs17576), CAT C262T (rs1001179), CYP2C19*2 G681A (rs4244285) and SPINK1 Asn34Ser (rs17107315) - to the development of SAP, infectious complications and adverse surgical outcomes in an ethnically homogeneous Uzbek cohort.